2011
DOI: 10.2478/v10152-011-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

Nursing knowledge as a response to societal needs: a framework for promoting nursing as a profession

Abstract: Introduction: As the population needs for health care at the local level become integrated into the global context, nurses are given the opportunity to make a significant contribution to the modernization of the healthcare system and gain importance and recognition from the political perspective. Nursing today is confronted with the needs and demands of both healthy and ill populations -these can be the result of changing demographics, new technologies, a growing awareness of the rights and voiced expectations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…Several researchers have reported that nurses have little knowledge of and an unfavorable attitude toward EBP. Many nurses do not recognize the concept of the term EBP or how to incorporate it into clinical practice [ 13 , 15 - 18 ]. Some other studies have reported that nurses have low self-efficacy in EBP activities.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported that nurses have little knowledge of and an unfavorable attitude toward EBP. Many nurses do not recognize the concept of the term EBP or how to incorporate it into clinical practice [ 13 , 15 - 18 ]. Some other studies have reported that nurses have low self-efficacy in EBP activities.…”
Section: Introductionmentioning
confidence: 99%
“…(3) zavezanost k izvajanju zdravstvenih storitev, ki koristijo posamezniku in skupnosti; (4) člani poklica zagotavljajo avtonomijo, zanesljivost in odgovornost delovanja v sistemu zdravstvene obravnave; (5) storitve so kontrolirane s standardi dela, spremljanjem kakovosti in izboljševanjem prakse, varnostjo pacientov in kodeksom etike delovanja; (6) člani poklica pripadajo profesionalnemu združenju in njegovim aktivnostim (Skela-Savič, 2009, 2017a, 2017b, 2017cSkela-Savič, et al, 2011, 2017a, 2017b. Navedbo »klinično delo« razumemo na primeru zdravstvene nege kot delo diplomirane medicinske sestre ali zdravstvenika z zdravo in bolno populacijo v vseh življenjskih obdobjih.…”
Section: Proučevani Okvir Profesionalizacije Zdravstvene Negeunclassified
“…Na izbor podatkov vpliva izbrani tematski okvir (Fitzpatrick, 2011, pp. 230-237); v našem primeru so to v uvodu navedeni elementi profesionalizacije zdravstvene nege (Skela-Savič, 2009, 2017a, 2017b, 2017cSkela-Savič, et al, 2011, 2017a, 2017b, ki smo jih poenostavili na razvojno obdobje v času poklicnega dela Angele Boškin. Poenostavljen tematski okvir zbiranja in razvrščanja podatkov ter njihove poznejše obdelave je obsegal: − znanje in sposobnosti v zdravstveni negi, − izobraževanje v zdravstveni negi, − izvajanje storitev v zdravstveni negi, − avtonomijo, zanesljivost in odgovornost izvajalcev, − kontrolo storitev in obstoječe standarde, − profesionalno združenje in aktivnosti.…”
Section: Tematski Okvir Zbiranja Podatkovunclassified
See 1 more Smart Citation
“…An important characteristic of professionalism is the integrity of systematic and generalized knowledge which must be used by professionals to solve diff erent problems (5,6). Th e basis of such knowledge is a good educational system which should provide such types of knowledge in accordance with high standards of socially recognized professionalism (11). Equally important for a profession is an established comprehensive system of leadership which is at least partially controlled by a professional association.…”
Section: Introductionmentioning
confidence: 99%